Size-dependent magnetic properties of nanocrystalline yttrium iron garnet powders - Rajendran, M.; Deka, Sasanka; Joy, Pattayil Alias; Bhattacharya, Asish K. (Journal of Magnetism and Magnetic Materials, 2006)
Yttrium iron garnet (YIG) powders with particle sizes of 9, 14, 25 and 60 nm have been synthesised and their magnetic properties have been studied as a function of particle size and temperature. The particles with sizes of 9 and 14 nm exhibited superparamagnetism. The blocking temperature (T-B) decreased with decreasing particle size, whereas the anisotropy constant (K) increased. The saturation magnetisation (M-s) decreased with decreasing particle size. These variations are attributed to large surface-to-volume ratios in nanoparticles where the surface moments are predominant. (c) 2005 Published by Elsevier B.V.
Keywords: anisotropy constant; Magnetism; Nanoparticles; Superparamagnetism; YIG